The incentive to invest in thermal plants in the presence of wind generation - Valeria Di Cosmo; Laura Malaguzzi Valeri (The Economic and Social Research Institute (ESRI), 2012)
In a deregulated market, the decision to build new thermal power plants rests with private investors and they will decide whether to invest on the basis of expected profits. This paper evaluates how such profits are affected by the increasing presence of wind generation. We use hourly historical data for the Irish Single Electricity Market, a compulsory pool market with capacity payments, and simulate future series of electricity shadow prices, bids of representative plants and wind generation. We estimate the correlation between shadow price and installed wind capacity on the basis of past data, finding a negative correlation. We then evaluate the effects of increased wind capacity on thermal power plants' expected profits. We find that increasing installed wind from the current level of 2000MW to about 3000MW causes a larger decrease in profits for baseload gas plants and a smaller decrease for less flexible coal-fuelled plants. The decrease in profits is of the order of 1 to 2 per cent.
Keywords: 330; electricity; generation incentives; simulation; wind generation; Ireland